Управление потоком мощности в тяговом приводе электропоезда при питании от контактной сети и инерционных накопителей энергии - Северин, Валерий Петрович; Оверьянова, Лилия Викторовна; Омельяненко, Ольга Владимировна (НТУ "ХПИ", 2015)
Рассматривается пригородный электропоезд с асинхронными тяговыми двигателями и бортовыми накопителями энергии. Предложена система управления перетоком мощности в исследуемом тяговом приводе с накопителем при питании от контактной сети. Показана стратегия системы управления, заключающаяся в обеспечении компенсации излишков или нехватки мощности тягового инвертора за счет управления током накопителя. Предложенная система управления потоком мощности позволит рекуперировать энергию в накопитель до полной остановки электроподвижного состава.

A commuter train with asynchronous traction engines and on-board energy storage devices is considered. Electromechanical flywheel storage with inverted DC machine and a solid-state switch was used as an energy storage unit. A scheme of a train traction aggregator was proposed. This scheme includes main parts, such as rotary-field motor and storage device, and solid-state devices - traction inverter and DC-DC chopper. Work of the scheme powered without trolley system was considered. Mathematical models of the energy exchange between traction engine and storage device were created. The results of numerical modeling which allow to estimate the energy efficiency of the system were received. Power flow-over controlling system in the traction mechanism (with storage device) powered by the trolley line was proposed for energy efficiency indexes increase. Controlling system strategy that is in providing compensation for excess or shortage of power of traction inverter by energy storage current management was demonstrated. Controlling system of the power flow that was proposed allows to restore energy into storage device until the full stop of the train.
Power flow control in electric traction drive powered by the contact network and inertial energy storage devices
Keywords: пригородный электропоезд; асинхронный электродвигатель; тяговый инвертор; система управления; control system; asynchronous motors; traction inverter